The aesthetic dimension of lighting in children's theater performances"The play Juha and the Donkey is an example" (Al-Academy, 2025)
Since the current research aims to identify the aesthetic dimension of lighting in children’s theater performances, therefore, the current research procedures tend to adopt the descriptive analytical method as it is the most appropriate scientific method to achieve the goal of the current research and reach the desired results from the analysis process.The community consists of children's theater performances (three theatrical performances) according to the limits of the current research, which in its context includes the method of lighting distribution, noting that the performances are produced by (students of the Department of Art Education, College of Fine Arts/2012). The researcher chose one theatrical performance as his research sample. (Juha and the donkey) in an intentional way. The researcher used the SPSS statistical package to extract the results, the most important of which are:1- The aesthetics of lighting in children’s theater performances are applied artistic processes aimed at creativity and innovation, as it contributes and positively influences the child’s effectiveness in order to arouse the motivation, purpose, and dream that struggle within him.The most important conclusions are:2- Theatrical lighting, in all its applications, helps in the correct construction of the child’s personality and contributes to the development of the mind and culture.